Hydrocodone Snorting Leading to Hypersensitivity Pneumonitis. Issue 3 (1st July 2016) - Pathak, Lakshmi Kant; Vijayaraghavan, Vimala
Abstract : We present a case of hypersensitivity pneumonitis caused by intranasal abuse of the prescription narcotic hydrocodone. The patient's clinical course was complicated by acute respiratory failure. A chest radiograph showed diffuse bilateral opacities. The patient was treated with noninvasive ventilation, a high dose of intravenous steroids, and bronchodilators, resulting in improvement of symptoms and radiographic appearance.